2000
DOI: 10.1038/sj.ejcn.1601110
|View full text |Cite
|
Sign up to set email alerts
|

Differences in resting energy expenditure between black and white smokers: implications for postcessation weight gain

Abstract: Objective: To examine differences in resting energy expenditure (REE) between black and white smokers in order to determine whether REE might contribute to postcessation weight gain. Design: Cross-sectional and prospective investigation of ethnic differences in REE. Differences in REE between black and white smokers were examined at baseline while all participants were smoking, and again during 2 weeks of abstinence from smoking. Setting: Memphis, Tennessee, USA. Subjects: Sixty-six black and 112 white smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…There were also a very small number of African-American smokers (six of 76 African-American women) in the Kimm et al study. Another study 25 found significantly lower REE in African-American and white smokers but did not analyze for gender differences. Since that study found no ethnic differences in the change in REE following smoking cessation, it is possible that baseline REE differences were due to ethnic REE differences previously noted in women [26][27][28][29][30][31] and also in men.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were also a very small number of African-American smokers (six of 76 African-American women) in the Kimm et al study. Another study 25 found significantly lower REE in African-American and white smokers but did not analyze for gender differences. Since that study found no ethnic differences in the change in REE following smoking cessation, it is possible that baseline REE differences were due to ethnic REE differences previously noted in women [26][27][28][29][30][31] and also in men.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] Most recently, this difference has also been noted in smoking women. 25 Smoking may, in some way, work to increase a depressed REE to a higher level in African-American women. If the women in the current sample are similar to those in The literature regarding how smoking affects REE is conflicting but the general consensus appears to be that smoking has no effect on chronic metabolic rate.…”
mentioning
confidence: 99%
“…Как правило, термическую реакцию на кофеин можно измерить через 30-150 минут после приема внутрь. У здоровых мужчин употребление кофеина в дозе от 200 до 350 мг приводило к увеличению среднего значения МП в груп пе на 7-11% [18].…”
Section: приводит ли употребление никотина или кофеина к ошибке в изм...unclassified
“…The goal of the intervention is to limit cessation-induced weight gain in order to improve BP control. Results from several studies indicate that the weight gain that occurs following smoking cessation is due primarily to increases in energy intake, although the loss of the acute increases in energy expenditure associated with repeated nicotine administration throughout the day also may play a role [28,[30][31]. Therefore, the intervention is aimed at reducing the positive energy balance that occurs after quitting smoking by limiting postcessation increases in energy intake and promoting increased energy expenditure through physical activity.…”
Section: Blood Pressure Control (Bpc) Interventionmentioning
confidence: 99%